Salmonella spv locus affects type I interferon response and the chemotaxis of neutrophils via suppressing autophagy. Issue 87 (April 2019) - Wang, Lidan; Li, Yangli; Liu, Yuanhui; Zuo, Lingli; Li, Yuanyuan; Wu, Shuyan; Huang, Rui
Abstract: Salmonella is a facultative intracellular pathogen that can cause significant morbidity and mortality in humans and animals. Salmonella plasmid virulence ( spv ) gene sequence is a highly conserved 6.8 kb region which exists in the plasmid of most pathogenic Salmonella . Autophagy is a degradation process of unnecessary and dysfunctional cytoplasm components to maintain cellular homeostasis, which could affect host inflammatory responses, such as type I interferon response. Type I interferon response can promote the antibacterial activity of macrophage as well as the secretion of cytokines and neutrophil chemokines. We previously reported that spv locus could suppress autophagy and the aggregation of neutrophils in zebrafish larvae. To explore the influence of spv locus on Salmonella escaping from the innate immune responses and the underlying mechanism, the models of Salmonella enterica serovar Typhimurium infected macrophages in vitro and zebrafish larvae in vivo were used in this study. The interactions among spv locus, autophagy, type I interferon response and the chemotaxis of neutrophils were investigated. Western blot was used to detect the expression levels of autophagy related proteins and RT-qPCR was used to measure the mRNA levels of type I interferon response and the neutrophil chemokines. The chemotaxis of neutrophils were observed by Laser Scanning confocal microscopy. Autophagy agonist Torin 1 was also involved to interfere the autophagy influx. Results showed that spv locus could restrain type I interferon response and the chemotaxis of neutrophils via suppressing autophagy, which provided substantial foundation to study the mechanism of Salmonella escaping the innate immunity. Highlights: Salmonella spv locus could affect type I interferon response via inhibiting autophagy in macrophages. spv locus could suppress the aggregation of neutrophils and augment the burden of Salmonella in larvae. spv locus could restrain type Ι interferon response and the chemotaxis of neutrophils via suppressing autophagy in larvae.